2021
DOI: 10.3389/fgene.2021.673229
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0002062 Promotes the Proliferation of Pulmonary Artery Smooth Muscle Cells by Regulating the Hsa-miR-942-5p/CDK6 Signaling Pathway

Abstract: Currently, new strategies for the diagnosis and treatment of hypoxia-induced pulmonary hypertension (HPH) are urgently required. The unique features of circRNAs have unveiled a novel perspective for understanding the biological mechanisms underlying HPH and the possibility for innovative strategies for treatment of HPH. CircRNAs function as competing endogenous RNAs (CeRNA) to sequester miRNAs and regulate the expression of target genes. This study aimed to explore the roles of hsa_circ_0002062 on the biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…Many studies have shown that miR-942-5p regulates cell proliferation and disease progression in different types of tumors ( Li et al, 2020 ; Wang et al, 2020 ; Gu et al, 2021 ; Zhang et al, 2021 ); these findings are consistent with our results, because PMECs dysfunction in PH is a cancer cell-like phenotype. However, Wang et al found that miR-942-5p could inhibit PASMCs proliferation in vitro ( Wang et al, 2021 ), which is inconsistent with our results; a possible reason for this is the difference in the cell types studied and the cell culture conditions. Evaluating the impact of miR-942-5p on PASMCs during PH development may also help clarify the basis for this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…Many studies have shown that miR-942-5p regulates cell proliferation and disease progression in different types of tumors ( Li et al, 2020 ; Wang et al, 2020 ; Gu et al, 2021 ; Zhang et al, 2021 ); these findings are consistent with our results, because PMECs dysfunction in PH is a cancer cell-like phenotype. However, Wang et al found that miR-942-5p could inhibit PASMCs proliferation in vitro ( Wang et al, 2021 ), which is inconsistent with our results; a possible reason for this is the difference in the cell types studied and the cell culture conditions. Evaluating the impact of miR-942-5p on PASMCs during PH development may also help clarify the basis for this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…14 In addition, accumulating evidence suggested that the aberrant expressions of circRNAs, such as hsa_circ_0002062, hsa_circ_0022342, and hsa_circ_0016070, contribute to PASMC proliferation for PAH development. [14][15][16] Functionally, circ-calm4 acts as a molecular sponge for miRNAs, modulating cell cycle progression and pyroptosis of PASMCs via miR-337-3p/Myo10 axis and miR-124-3p/PDCD6 axis, respectively. 24,25 Furthermore, circRNAs have also been reported to regulate human pulmonary artery endothelial cells (PAEC) function in PAH development.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of has_circ_0002062 prevented cell proliferation and migration in PASMCs by acting as a ceRNA targeting miR-942-5p/CDK6 axis. In addition, CDK6 inhibition by AAV in vivo prevented pulmonary vascular remodeling in a hypoxia-induced PH model [ 129 ], which suggests that the downstream target of has_circ_0002062 shows therapeutic potential. Thus, manipulation of has_circ_0002062 may be a promising therapeutic strategy for PH.…”
Section: Circrnasmentioning
confidence: 99%